Pengaruh Air Leri terhadap Pertumbuhan Vegetatif Tanaman Cabai Rawit (Capsicum frutescens) - Royani, Ida; Imran, Ali; Dharmawibawa, Iwan Doddy (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Leri water is a household waste from washing rice, known to contain various important nutrients, such as vitamins A, C, B1, carbohydrates, phosphorus, potassium, magnesium, nitrogen, and iron. The nutritional content in rice washing water can be used to support the growth and development of chili plants. This study aims to determine the effect of leri water on the growth of plant height and number of leaves of cayenne pepper plants (Capsicum frutescens L). The design used was a Completely Randomized Design (CRD) consisting of 5 treatments with 3 replications P1 0%, P2 25%, P3 50%, P4 75%, and P5 100%. P1 (without using leri water), P2 (250ml leri water + 750 plain water), P3 (500ml leri water + 500ml plain water), P4 (750ml leri water + 250ml plain water), and P5 (without using plain water). The variables observed were plant height and number of cayenne pepper leaves. The results of the study showed that the provision of leri water had an effect on the vegetative growth of cayenne pepper plants (Capsicum frutescens L.), the best results were seen in the P5 treatment with 100% leri water without a mixture of ordinary water, and the lowest results were in the P1 treatment without using leri water.